Sound Art and Music Philosophy, Composition, Performance. - Dack, John (Cambridge Scholars Publisher, 2020)
This volume explores the mutually beneficial, but occasionally uneasy, relationship between sound art and music. It reveals how practices and theories associated with these art forms frequently result in corroboration, and contains chapters from both practitioners and theoreticians who work in areas where innovative synergies between sound art and music can be identified. Although practice and theory are inseparable, discourses surrounding practice are elusive but informative, and, as such, are given particular recognition and exploration in this volume. Taken as a whole, the book provides a s.